Analisis Kelayakan Finansial Pembesaran Benur Udang Vanname (Litopenaeus Vannamei) dari Naupli Sampai Post Larva, di BPBAP Situbondo, Instalasi Tuban Jawa Timur - Adi Pramono, Mahasyin; Purnamasari, Ika; Anam, M. Khairul (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2023)
The aim of this study is to analyze the amount of asset costs, total production costs and vannamei shrimp farming income which will later be calculated by calculating the financial feasibility analysis at the Tuban Installation, East Java. The method used is a quantitative descriptive analysis method with data collection techniques using observation, interviews, active participation and discussion, searching for literature and documentation of activities. The results of this study indicate that the results of financial calculations by stocking 30,000,000 Naupli larvae require a production cost of IDR 59,315,194 for rearing them from Naupli stage to post larval stage, total income of IDR 101,145,000, net profit of IDR 41,829. 806 has a profit rate of 70%, profitability = 17% (less efficient because <25%), R/C = 1.7 (feasible because > 1), BEP price (Rp) = Rp 8 and production BEP = 3,954,346 tails. But in practice it needs to be improved because in calculating profitability it is at <25%, which means it is less efficient. So that in order for these activities to have profitability above 25%, it is necessary to improve efficiency in terms of enhancing production facilities and means